Pengaruh Metode Program Pelatihan Terjemah Al-Qur’an Safinatul Huda terhadap Kemampuan Santri dalam Menerjemahkan Al-Qur’an Di Madrasah Diniyah Awaliyah Al-Balagh - Agustinova, Isnadila; Firdaus, Mohammad (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Studying the Quran is an obligation for every Muslim around the world, including Indonesia. Indonesia has a population that is predominantly Muslim. One of the core things in the values of Islamic teachings is how followers of the Islamic religion can practice what is contained in the source of their teachings, namely the Qur'an and Hadith. Learning Al-Quran Hadith is one part of the existing Islamic Religious Education group starting from the madrasah level of Ibtidaiyah, Tsanawiyah to the Aliyah level. The Safinatul Huda (Safinda) PPTQ method is a method of learning the translation of the Quran as well as its grammar directly from the Arabic language in a simple, easy, and practical way. The formulation of the problem taken in this study is: (1) Is there an influence of the PPTQ safinatul huda method on the ability of students to translate the Qur'an at the Al-Balagh Pronojiwo-Lumajang madrasah diniyah al-Balagh? (2) How much influence does the PPTQ safinda method have on the ability of students to translate the Qur'an at the Al-Balagh Pronojiwo-Lumajang madrasah dinniyah? In this study, the method used is a quantitative research method consisting of two variables, namely the Safinatul Huda Method (variable X) and Translation Ability (variable Y). The data collection technique uses a questionnaire method for variable X, and uses a test for variable Y, the subjects of this study were taken from 30 respondents. And for data analysis, the critique price table used is r and calculated using the help of SPSS with a simple linear regression formula. The results of the study show that the PPTQ safinatul Huda method has a positive influence on the ability of students to translate the Qur'an. This is evidenced by the value in the results of the T test which shows that t calculates > t table (4,420>1,701) and sig. 0.000<0.05. So that Ha was accepted and Ho was rejected and it can be concluded that the safinatul huda method partially has an influence of (482) 48.2% while the remaining 51.8% is the influence of other variables outside the study